Problematics of Decentralization in the Field of Health Law in the Autonomous Era - taufik,, Iqbal; Baranyanan, Soeleman Djaiz; Irham, Muhammad (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Based on positive law, which applies in Indonesia, decentralization has "chosen" to give up some of its authority to autonomous regions. The delegated authority is very broad, because in Law Number. 23 of 2014 uses a residual system when determining what is the authority of local governments. With the residual system, the central authorities have been clearly defined in advance, while the rest are autonomous regions. Therefore, authority in the health sector has become an autonomous regional government authority, because that authority is not determined as the authority of the central government. On the one hand this benefits the local government, because by using its authority, the regional government can regulate the health sector according to its aspirations and capabilities. This research was approached in terms of legal science, both at the dogmatic level, legal theory, and legal philosophy. In this study also used a normative legal approach or library law, namely legal research conducted by examining library materials or secondary data. Normative legal research or literature includes research on semantic law, research on the degree of vertical and horizontal synchronization, comparison of law and history of law. Research on legal principles is carried out by interpreting the legal norms formulated in laws and regulations relating to local government in Indonesia. Based on this research study, it can be concluded that in terms of law and policy as well as the scope of authority of regional governments that support regional autonomy in the health sector, it is still unclear and inconsistent in the description of the functions and authority of regional governments in the health sector.Keywords:Decentralization; Health Law; Regional Autonomy